2021
DOI: 10.1002/admi.202100355
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Trap‐State Density Enhancement in Flash Infrared Annealed Perovskite Layers

Abstract: dye-sensitized solar cells. The most studied perovskite compound is methylammonium lead iodide (CH 3 NH 3 PbI 3 , MAPI), although it is not moisture resistant and may be hazardous to the environment. Lee et al. [2] showed that perovskite thin layers could be used directly for harvesting solar radiation similar to inorganic semiconductors. Since then, tremendous advances have been made in optimizing perovskite solar cells (PSCs), with power conversion efficiencies (PCE) reaching 25.5% and thus coming to the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Among optical methods, photoluminescence (PL) spectroscopy is commonly used, as PL efficiency is closely related to PCE. ,, However, the layer morphology and structure or the chemical composition of individual phases cannot be unambiguously determined by PL during perovskite formation. X-ray scattering methods are more suitable in this respect, but their in situ utilization is limited in laboratory conditions. Typically, synchrotron-based scattering techniques, such as grazing-incidence small/wide-angle X-ray scattering (GI-SAXS/WAXS) , or the coplanar lab-based X-ray diffraction are employed, both having their pros and cons. , X-ray diffractometers are easily accessible, but the beam intensity might not be sufficient to detect fast processes that require short integration time.…”
mentioning
confidence: 99%
“…Among optical methods, photoluminescence (PL) spectroscopy is commonly used, as PL efficiency is closely related to PCE. ,, However, the layer morphology and structure or the chemical composition of individual phases cannot be unambiguously determined by PL during perovskite formation. X-ray scattering methods are more suitable in this respect, but their in situ utilization is limited in laboratory conditions. Typically, synchrotron-based scattering techniques, such as grazing-incidence small/wide-angle X-ray scattering (GI-SAXS/WAXS) , or the coplanar lab-based X-ray diffraction are employed, both having their pros and cons. , X-ray diffractometers are easily accessible, but the beam intensity might not be sufficient to detect fast processes that require short integration time.…”
mentioning
confidence: 99%
“…The corresponding line‐cut profiles in the in‐plane and out‐of‐plane directions are displayed in Figure 2B,C, respectively. It was found that two predominant scattering rings at ~1.0 and ~2.2 Å −1 , which correspond to the (1 1 0) and (2 2 0) planes of perovskite crystals, respectively 41,42 . Moreover, the relative intensities (I) of (1 1 0) and (2 2 0) in the in‐plane direction and the ratios of I (110) / I (220) for control and TDCA modified films are calculated to be 1.12 and 0.59, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…It was found that two predominant scattering rings at $1.0 and $2.2 Å À1 , which correspond to the (1 1 0) and (2 2 0) planes of perovskite crystals, respectively. 41,42 Moreover, the relative intensities (I) of (1 1 0) and (2 2 0) in the inplane direction and the ratios of I (110) /I (220) for control and TDCA modified films are calculated to be 1.12 and 0.59, respectively. TDCA-treated film exhibited a relatively more preferred in-plane orientation growth in the (1 1 0) direction than the control film, implying that TDCA can promote preferential orientation and crystallization of perovskite films, 43 which could be one of the important consequences in improving final PSCs photovoltaic performance.…”
Section: Resultsmentioning
confidence: 99%
“…Such a study used a custom-designed FIRA chamber. 280 Although some inspiring examples have been demonstrated so far comprising the investigation of MAPbI 3 , FAPbI 3 , mixedcation, and all-inorganic perovskites prepared from bladecoating and slot-die, there is a continued need for developing and using in situ and operando techniques for the characterization of scaling-relevant compositions. It is likely that MAPbI 3 will not be the best perovskite formulation for upscaling, which will possibly rely on FA-rich structures or complex alloys.…”
Section: Scalable Methodsmentioning
confidence: 99%